Effect of organic fertilizers on CH4 and N2O production from organic paddy field. Issue 1 (April 2021) - Anshori, A; Sunarminto, B H; Haryono, E; Pramono, A; Mujiyo,
Abstract: Organic fertilizer potentially results in healthy soils and sustainable agriculture. Organic fertilizer is a nutrients source in organic farming. Organic fertilizer application affects CH4 and N2 O production. CH4 and N2 O production affect increasing greenhouse gas emission concentration, global warming and further climate change. This study aimed to determine organic fertilizers effect on CH4 and N2 O production from organic paddy fields. Five types of organic fertilizer namely mixed compost (MC), cow manure (CM), cow manure compost (CMC), straw compost (SC) and solid biogas waste (SBW) were added to paddy soil and determined CH4 and N2 O production. The result showed that CH4 and N2 O production were affected by organic fertilizer addition. CH4 production was 109.52 mg kg soil -1 day -1 and N2 O production was 1.70 mg kg soil -1 day -1 . The lowest production of both gasses was in SBW treatment. CH4 production was 177.21 mg kg soil -1 day -1 and N2 O production was 2.80 mg kg soil -1 day -1 . The highest was in soil with cow manure (CM) treatment. CH4 and N2 O production correlated positively with organic carbon and Carbon and Nitrogen ratio (C/N) of organic fertilizers (p < 0.05). Application of solid biogas waste (SBW) with drainage treatment on 10 th day and composting are the best effort to mitigate CH4 and N2 O production.